2021
DOI: 10.1063/5.0067895
|View full text |Cite
|
Sign up to set email alerts
|

Coupled Faxen relations for non-uniform slip Janus spheres

Abstract: A non-uniform surface slip can cause a symmetry breaking in the geometry of an otherwise homogeneous spherical particle to give rise to an anisotropic hydrodynamic resistance to the particle. Here, we develop a more general theoretical framework capable of decoding the surface-pattern-dependent hydrodynamic features for single heterogeneous spheres having arbitrary non-uniform slip length distributions in small variations, especially for those of weakly stick–slip or slip–slip Janus spheres in either the two-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…To use (2.25) for computing the stresslet of a stick–slip sphere, it is more convenient to expand the spatially varying part of the slip length in terms of surface harmonics (Premlata & Wei 2021). As to concerning how many terms are required to faithfully describe impacts of slip anisotropy on the stresslet, we need an additional rule, which is guided by general considerations, for constructing an anisotropic stresslet.…”
Section: Re-expressing Slip Anisotropy In Terms Of Surface Momentsmentioning
confidence: 99%
See 4 more Smart Citations
“…To use (2.25) for computing the stresslet of a stick–slip sphere, it is more convenient to expand the spatially varying part of the slip length in terms of surface harmonics (Premlata & Wei 2021). As to concerning how many terms are required to faithfully describe impacts of slip anisotropy on the stresslet, we need an additional rule, which is guided by general considerations, for constructing an anisotropic stresslet.…”
Section: Re-expressing Slip Anisotropy In Terms Of Surface Momentsmentioning
confidence: 99%
“…However, it is not clear how both the stresslet and torque are determined by the stick–slip pattern of the sphere. In particular, if the surface of the sphere is not equally partitioned by stick and slip parts, it will actually comprise both surface dipole and quadrupole contributions (Premlata & Wei 2021). We recently showed that these surface moments can have rather distinct impacts on the force and torque on a non-uniform slip sphere (Premlata & Wei 2021).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations